2008
DOI: 10.1128/jb.00860-08
|View full text |Cite
|
Sign up to set email alerts
|

The Type III Pantothenate Kinase Encoded by coaX Is Essential for Growth of Bacillus anthracis

Abstract: In Bacillus anthracis, the novel type III pantothenate kinase (PanK Ba ; encoded by coaX) catalyzes the first committed step in coenzyme A biosynthesis. We have demonstrated by analyzing the growth characteristics of a conditional coaX mutant that PanK Ba is an essential enzyme, thus contributing to its validation as a new antimicrobial target.Coenzyme A (CoASH) (20) is the major low-molecularweight thiol in Bacillus anthracis (25); the tripeptide thiol glutathione (8) is absent in all species of Bacillus anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…This has been found to be true in B. subtilis, wherein it has been demonstrated that the presence of either CoaA or CoaX permits the cell to be viable (Yocum & Patterson, 2004). However, in a related bacterium, B. anthracis, which possesses type II and III isoforms of pantothenate kinase (Yang et al 2006), the coaX gene was found to be essential even in the presence of type II isoform of pantothenate kinase (Paige et al, 2008), which led the authors to propose CoaX as a drug target for developing inhibitors (Paige et al, 2008). Whether the type II pantothenate kinase of B. anthracis is also essential or not is not clear at this moment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This has been found to be true in B. subtilis, wherein it has been demonstrated that the presence of either CoaA or CoaX permits the cell to be viable (Yocum & Patterson, 2004). However, in a related bacterium, B. anthracis, which possesses type II and III isoforms of pantothenate kinase (Yang et al 2006), the coaX gene was found to be essential even in the presence of type II isoform of pantothenate kinase (Paige et al, 2008), which led the authors to propose CoaX as a drug target for developing inhibitors (Paige et al, 2008). Whether the type II pantothenate kinase of B. anthracis is also essential or not is not clear at this moment.…”
Section: Discussionmentioning
confidence: 99%
“…1, 6, genomic DNA; 2, 7, RT template; 3, 8, RT-minus template; 4, 9, no template; 5, molecular size marker. (Dunn & Snell 1979;Vallari & Rock, 1987;Wood & Friedman, 2000;Liberati et al, 2006: Paige et al, 2008, it can be speculated that either of the two kinase coding genes (coaA or coaX) could potentially be capable of providing the essential enzymic function for the survival of M. tuberculosis. In order to prove whether either of them could keep the cells alive in the absence of other isoforms (as in B. subtilis) or only one is essential even in the presence of the other isoform (as in B. anthracis), we attempted to inactivate the coaA and coaX genes of M. tuberculosis individually.…”
Section: Coaa (Rv1092c) Is Essential For the Survival Of M Tuberculosismentioning
confidence: 99%
See 2 more Smart Citations
“…For this reason, generation of stable mutants by allelic exchange is the preferred method of isolating mutants in B. anthracis . This method of isolating single crossover insertion of plasmids has been used to examine whether particular genes of interest are essential (Paige et al, 2008 ); the inability to isolate viable cells when both levels of selection are administered is consistent with the conclusion that the genes in question are essential for growth. These protocols have also been adapted for regulatory studies of genes in B. anthracis .…”
Section: Mutants Derived From Simple (Campbell -Type) Plasmid Insertionmentioning
confidence: 99%